Sectoral Impact and Current Coping Mechanisms: Water Resources and Agriculture - KASDI SUBAGYONO; ERNI SUSANTI (Indonesian Center for Agriculture Land Resource Development, 2009)
Available water resources and its quality in Indonesia have been deteriorated as an impact of climate change (and/or) environmental degradation. This could affect on farming processes particularly and agricultural development in general. Virtual available surface water gives a figure that available water decreased temporally and spatially. For instance, in Java island with cover 65% of total population only has 4.5% of the total available water in the country. Agriculture is the biggest use of water (about70%), but it will be difficult for farmers to accomplish water requirements. Other users such as domestic (about 6%), industry (about7%), and municipal (about 4%) are also the major users of water in the country, which may raise a conflict among the users in covering the needs. Current mechanisms to cope climate change in water resources management has been executed through adaptation and mitigation measures for supporting farming system. Integrated water resources management plays critical role in coping climate change. This includes prioritizing water requirements, water harvesting, water conservation, appropriate water allocation, and pollution control. For sustainable farming system development, mitigation strategy should also be included in themechanism covering practices of intermittent irrigation to over come high rate of methane emission. Combining water management and tolerance crops to drought and submergence conditions is very valuable in implementing the mechanisms.